KEBIJAKAN PEMERINTAH KABUPATEN BADUNG TENTANG OPERASIONAL HIBURAN MALAM GROUND ZERO DI LEGIAN, KUTA - I Putu Andrey Febri Astika; Ni Luh Kerti Pujani (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2015)
ABSTRACT This research will discuss about the Badung Government Policy About Operation Nightlife Ground Zero in Legian, Kuta. This study seeks to describe the development of tourism in Badung regency, a description of the policies established by the Government of Badung regency which are mapped to the employers area nightclubs Ground Zero in Jalan Legian, Kuta. . Types and sources of data are qualitative and quantitative data as well as primary and secondary data. Data was collected by observation, in-depth interviews, and library research. Determination techniques and informers samples used in this study is the purposive sampling method of obtaining information or a complete and in-depth data. Data analysis techniques used in this study is qualitative research means research that produces descriptive data in the form of writing or speech, words, and behaviors that can be observed by the researchers. From the discussion of the research on